Gastro protective activity of Momordica cymbalaria fruits against experimentally induced gastric ulcer in rats - P. Bharathi Dhasan; M. Jagadeesan (International Journal of Phytomedicine, 2010)
The effect of petroleum ether, chloroform and methanol extracts of unripe fruits of Momordica cymbalaria (Cucurbitaceae) was investigated in rats to evaluate the anti-ulcer activity by using three models, i.e. aspirin, alcohol and pyloric ligation induced gastric ulcer in rats. The parameters taken for assessing the anti-ulcer activity were volume of gastric secretion, PH, free acidity, total acidity and ulcer index. The results of the study revealed that the methanol extract of Momordica cymbalaria fruits had significantly (P < 0.001) reduced the volume of gastric acid secretion, PH, free acidity, total acidity and ulcer index with respect to control.